Health Goal Attainment of Patients With Chronic Diseases in Web-Based Patient Communities: Content and Survival Analysis - Song, Jiahe; Xu, Pei; Paradice, David B (JMIR Publications, 2020)
BackgroundActivities directed at attaining health goals are a major part of the daily lives of those fighting chronic diseases. A proliferating population of patients with chronic diseases are participating in web-based patient communities, wherein they can exchange health information and pursue health goals with others virtually. ObjectiveIn this study, we aimed to understand the effect of participation in social media-enabled web-based patient communities on health goal attainment. In particular, we studied the antecedents of health goal attainment in terms of social support and self-reflection in web-based patient communities. MethodsThis data set consists of web-based health management activities of 392 patients across 13 health support groups, that is, groups with medical issues such as high blood pressure, diabetes, and breast cancer; the data of the activities were collected from a leading web-based patient community. Content analysis was used to code the social interactions among the patients on the web-based platform. Cox regression for survival analysis was used to model the hazard ratio of health goal attainment. ResultsOur analysis indicated that emotional support from web-based patient communities can increase patients' probability of achieving their goals (hazard ratio 1.957, 95% CI 1.416-2.706; P<.001) while informational support does not appear to be effective (P=.06). In addition, health-related self-reflection increases the patients' likelihood of goal attainment through web-based patient communities (hazard ratio 1.937, 95% CI 1.318-2.848; P<.001), but leisure-oriented self-reflection reduces this likelihood (hazard ratio 0.588, 95% CI 0.442-0.784; P<.001). ConclusionsSocial media-enabled web-based platforms assist health goal management via both social interaction and personal discipline. This study extends the understanding of web-based patient communities by investigating the effects of both social and cognitive factors on goal attainment. In particular, our study advocates that health goals relating to chronic conditions can be better managed when patients use the facilities of web-based health communities strategically.